2014
DOI: 10.1007/s00192-014-2553-0
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of excised midurethral sling mesh

Abstract: Midurethral sling mesh excised for voiding dysfunction demonstrates elevated levels of inflammation compared to mesh that is excised for pain and/or exposure. The vaginal tissue fibrosis and giant cell reaction are similar in patients who undergo mesh excision for voiding dysfunction and pain, and/or mesh exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Consistent with prior studies in the literature examining pathology findings of explanted mesh, 9,10,15,19 we predominantly noted fibrosis (98%), chronic inflammation (54%), and foreign-body giant cell reaction (66%). The elevated percentage of fibrosis may be explained by the fact that it is part of the normal reaction to a mesh material, and over time, fibrotic encapsulation is the expected response to a foreign body.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with prior studies in the literature examining pathology findings of explanted mesh, 9,10,15,19 we predominantly noted fibrosis (98%), chronic inflammation (54%), and foreign-body giant cell reaction (66%). The elevated percentage of fibrosis may be explained by the fact that it is part of the normal reaction to a mesh material, and over time, fibrotic encapsulation is the expected response to a foreign body.…”
Section: Discussionsupporting
confidence: 89%
“…However, it is important to note that 35% of women in this cohort experienced pain in the absence of mesh exposure or erosion. This may be explained by the histopathologic findings and inflammatory response that have been observed with the use of transvaginal polypropylene mesh, which may invoke pain without clinical evidence of obstruction or erosion [30][31][32]. Prior studies have shown that 60% to 80% of women have relief of pain after mesh removal (TVM and/or sling mesh) [15,22], and our results are consistent with these reports.…”
Section: Characteristics Of Women Undergoing Mesh Removalsupporting
confidence: 90%
“…Histological study of human tissue from patients having undergone revision, removal or planned biopsy following transvaginal mesh or midurethral sling demonstrated a mild persistent inflammatory reaction to polypropylene [67,[140][141][142][143][144]. This effect has been seen in prospective vaginal punch biopsies showing increased macrophages and mast cell infiltration 2 years after transvaginal mesh placement [140].…”
Section: Histologymentioning
confidence: 91%
“…Review of pathology reports from explanted vaginal mesh specimens included the diagnostic terminology 'fibrous/fibrosis' in 70.1% of explants, 'foreign body giant cell reaction' in 18.8% and 'inflammation' in 10.4% [143]. When midurethral sling explants were examined, inflammation was significantly higher in patients with only voiding dysfunction as opposed to those with mesh exposure or a mixed presentation [142]. The observation that there are different tissue reactions based on presentation is further supported by the work of Nolfi et al When examining polypropylene vaginal explants removed after 4.5-93 months, patient-reported pain was associated with profibrotic interleukin-10 and M2 'proremodelling' macrophages, while those presenting with erosion had an increase in proteolytic matrix metalloproteinase-9, indicating degradation [144].…”
Section: Histologymentioning
confidence: 99%